PERAN IBADAH SOLAT SEBAGAI MANAGEMENT STRESS PADA WANITA PASCA ABORSI - Selvina Ayudia; Purnomosidi, Faqih; Anniez Rachmawati Musliffah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores how prayer helps women in Solo Raya who experience stress after non-procedural abortions achieve psychological peace. This research used a qualitative phenomenological method with data collection through interviews and observations. Partner pressure and social stigma led to abortion, which led to guilt, somatic symptoms, and suicidal ideation. Initially, non-adaptive coping mechanisms, such as isolation, transformed into adaptive coping mechanisms, with prayer providing a sense of calm, forgiveness, and emotional strength rather than hobbies or social support. The sequence of ablutions made the informants feel cleaner and purer. Continuing with dhikr and prayer, inner peace enveloped them. The results of the prayers also made the informants feel more optimistic in living their lives and were able to avoid anxiety and stress.